Financial Stability of Electricity Companies in the Context of the Macroeconomic Instability and the COVID-19 Pandemic - Savchina, Oksana V.; Pavlinov, Dmitriy A.; Savchina, Olga V. (International Journal of Energy Economics and Policy, 2021)
The electricity sector is an important part of any country's economy as it holds a cross-sectoral importance and produces a socially significant product for residents and industries. Economically, the sector is less vulnerable during world crises, receiving many variations of the state support. Both world electricity consumption and electricity generation have grown steadily over 2007-2019, with China, USA, India, Russia, Japan, Canada, South Korea, Germany, Brazil and France being world market leaders. This article analyzes the current state and the main trends of the development of the electricity industry as a whole and the financial stability of its companies. The United States and Russia, with similar functioning market models, were chosen to assess. The analysis of the financial stability of PJSC Inter RAO and Exelon Corp, two electricity giants in Russia and in the United States, has shown that they demonstrate stable results: Exelon Corp is more profitable while PJSC Inter RAO is less dependent on financing from creditors. Overall, electricity companies and the industry as a whole should not suffer much from the COVID-19 pandemic: many financial support measures have been developed in both countries, helping the sector to recover to 2019 levels by 2021. Keywords: energy sector, electricity industry, economic and financial crisis, coronavirus pandemic (COVID-19), low-carbon economy, financial stability. JEL Classifications: G30, L94, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.11575